'Survivorship' in prostate cancer II: the need for ongoing patient support. Issue 4 (22nd July 2013) - Kirby, Roger; Forster, Paul; Sharp, Owen
Abstract With increasing numbers of men living with prostate cancer for many years, there is a growing need for improved support in the long term. Copyright © 2013 John Wiley & Sons